The Development of Types and Measurement of Banking Risk: A Literature Review - Tri Hanani (Universitas Teknologi Yogyakarta, 2022)
Banking is one of the vital industries of every country. Healthy banking supports the stability of a country's economy so banking risks are crucial to be analyzed. The purpose of this article is to identify banking risk and its measurement as well as to explore the comparison of theories and empirical studies of risk in large and small banks. This article was compiled using the literature review method from several studies related to bank risk and its measurement published in the period 1997 to 2020. This study shows that banking risk is currently divided into eight types, namely: credit risk, market risk, liquidity risk, operational risk, compliance risk, legal risk, reputation risk, and strategic risk. Several theories developed in the banking sector include the unstable banking hypothesis, the too-big-to-fail hypothesis, the agency cost hypothesis, and the small bank advantage hypothesis.